2017
DOI: 10.1016/j.combustflame.2017.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Study of the low-temperature reactivity of large n-alkanes through cool diffusion flame extinction

Abstract: The low-temperature oxidation of hydrocarbon fuels has received increasing attention as advanced engines seek to operate in less conventional combustion regimes. Large n-alkanes are a notable component of many real transportation fuels and possess strong reactivity in this important low-temperature range. These n-alkanes have been studied extensively in various canonical kinetic experiments but seldom in systems with strong coupling between lowtemperature chemistry, transport, and heat release. To address this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 100 publications
2
20
0
Order By: Relevance
“…Unfortunately, since many of these studies were either limited by the intermittency of cool flames or strongly affected by the flame wall thermal and chemical interaction, few studies have been made on effects of pressure, heat loss, mixture dilution, and chemistry-transport coupling on the propagation limits and speeds of cool flames. Recent counterflow cool flame studies [18,24,25] using ozone sensitization to enhance the low temperature chemistry have provided some quantitative experimental data of the extinction limits and structures of diffusion and premixed cool flames. It was observed experimentally that a cool flame can be sustained beyond the extinction limit of a hot flame.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, since many of these studies were either limited by the intermittency of cool flames or strongly affected by the flame wall thermal and chemical interaction, few studies have been made on effects of pressure, heat loss, mixture dilution, and chemistry-transport coupling on the propagation limits and speeds of cool flames. Recent counterflow cool flame studies [18,24,25] using ozone sensitization to enhance the low temperature chemistry have provided some quantitative experimental data of the extinction limits and structures of diffusion and premixed cool flames. It was observed experimentally that a cool flame can be sustained beyond the extinction limit of a hot flame.…”
Section: Introductionmentioning
confidence: 99%
“…Another significant note is that the ignition delay times of n-nonane, n-decane, n-undecane, and n-dodecane are almost identical, despite the increasing length of the carbon chain. There has been increasing research in the lowtemperature combustion regime as more engine manufacturers have been seeking this operating condition to improve fuel efficiency and decrease harmful emissions, e.g., [35]. N-alkanes, especially larger n-alkanes, are known to be reactive during low-temperature combustion [36].…”
Section: Chemical Kinetic Models and Properties Of Gasoline Hydrocarbmentioning
confidence: 99%
“…Since n-alkanes are used to mimic the combustion characteristics of gasoline fuel; e.g., [19], it is crucial to understand if the surrogate models will accurately model the fuel during low-temperature oxidation. The chain length of the n-alkane has a tremendous effect on the cool flame reactivity and current gasoline surrogate models have poor results when it comes to modeling oxidation behavior in these regions, e.g., [35].…”
Section: Chemical Kinetic Models and Properties Of Gasoline Hydrocarbmentioning
confidence: 99%
“…The results of these studies have shown that the low-temperature chain-branching sequence (peroxy chemistry) present in many hydrocarbons and oxygenates is capable of producing enough radicals and heat release to sustain stable cool flames across a variety of conditions. These experiments have also provided important validation targets for the development of chemical kinetic models at low temperatures 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent numerical simulations have shown that cool flames can play an important role in the ignition [13][14][15] , stabilization 16 , and propagation 17 of turbulent flames. However, numerical prediction of cool flame behavior is extremely sensitive to the chemical kinetic model employed, and many widely used models that 2 American Institute of Aeronautics and Astronautics perform well for high-temperature flames are incapable of describing cool flames accurately 8 . Therefore, the experimental measurement of turbulent cool flames can provide valuable insights into the modeling of turbulencechemistry interactions at low temperatures.…”
Section: Introductionmentioning
confidence: 99%